Medication Error - Shah (Gupta), Bimala (Journal of Nursing Education of Nepal, 2022)
Background: Medication errors are one of the patient safety problems with a high prevalence in several countries, and often involve a lack of collaborative communication between health professionals, including doctors, pharmacists, and nurses. This article aimed to review about medication error in hospital settings. Methods: Literature review was done through searching electronic database like PubMed, Research Gate, Google Scholar, and Science Hub and create library via Zotero software to save data. Results: The review article found most of the medication error occurred in medical and surgical units of the hospital and in morning shift, the most of the nurses are accountable for avoiding medication errors, and it happens mostly during administering the drugs to the patients. Conclusion: Medication errors and difficulties associated to nurses, doctors and pharmacists in hospital settings must be carefully monitored in order to maintain patients’ safety. Keywords: Literature review, medication error, nurses, safety